IMPLEMENTATION OF EXPERIENTIAL LEARNING METHODS ON STUDENT CHARACTER ESTABLISHMENT - Widya Septiana; Burhanudin Burhanudin; Fathul Jannah (IAIN Padangsidimpuan, 2023)
Abstract The purpose of this research is to understand the experiential learning method in learning the moral creed on the formation of student character. This type of learning is directed at efforts to help students become aware of their thinking processes. In addition, this study also attempted to conduct a critical analysis related to the formation of student character in learning a good moral creed in student character. This study uses someone's research and collects data from someone. As for education, basically, the interaction of a teacher and his students, and students are also required to be active in reading education. Educational actors must also have procedures for carrying out the education system, Keywords: faith; morals; experiential learningAbstrak Tujuan penelitian ini adalah untuk memahami metode experiental learning pada pembelajaran akidah akhlak terhadap pembentukan karakter siswa. Jenis pembelejaran ini diarahkan pada upaya untuk membantu peserta didik agar sadar terhadap proses berfikirnya. Selain itu, penelitian ini juga berusaha melakukan analisis kritis berkaitan dengan pembentukan karakter siswa dalam pembelajaran akidah akhlak yang baik dalam karakter siswa. Penelitian ini mengunakan penelitian seseorang dan mengumpulkan data dari seseorang. Adapun pendidikan pada dasarnya interaksi seseorang guru dan peserta didiknya dan peserta didik juga duharuskan untuk harus giat dalam membaca pendidikan . Pelaku pendidikan juga harus harus memiliki prosedur dalam melakukan sitem pendidikan tersebut, di masa pandemi ini juga bagus untuk kita melakukan penerapan metode pendidikan experiential learning karena pembelajaran dilakukan dengan daring , jadi mungkin pembentukan akhlak pada peserta didik dengan mengkoordinir orang tua agar bisa mengawasi anak dirumah. Kata Kunci: akidah; akhlak; experiential learning